Evaluation of the antileishmanial potency, toxicity and phytochemical constituents of methanol bark extract of Sterculia villosa - Antu Das; Manash C. Das; Niranjan Das; Surajit Bhattacharjee (Pharmaceutical Biology, 2017)
Context: Visceral leishmaniasis is a protozoan disease caused by Leishmania donovani parasite. The genus Sterculia (Malvaceae) possesses ethnobotanical potential against this protozoan infection. Objective: Determining the potential role of methanol bark extracts from Sterculia villosa Roxb (SVE) and its phytoconstituents against Leishmania donovani promastigotes. Materials and methods: SVE was analysed by TLC, UV–Vis, IR spectroscopy and biochemical assays. Antileishmanial potential of SVE (0.5–130 μg/mL for 72 h) was characterized by MTT assay. Fluorescent microscopy was performed to validate the IC50 dose. To determine the effect of SVE on promastigotes, reactive oxygen species (ROS) and superoxide generation, lipid peroxidation and DNA fragmentation assays were performed. Molecular aggregation of compounds was determined by atomic force microscopy (AFM). Extent of cytotoxicity of SVE at IC50 dose was determined against RAW 264.7 macrophages, peritoneal macrophages and murine RBCs. In vivo cytotoxicity of SVE was evaluated in BALB/c mice. Result: SVE exhibited reverse dose dependent antileishmanial activity when 130–0 μg/mL doses were tested against promastigotes. The IC50 and IC70 values were found to be 17.5 and 10 μg/mL, respectively. SVE at IC50 dose demonstrated elevated level of ROS, superoxide, lipid peroxidation and DNA fragmentation against promastigotes with no cytotoxicity. AFM analysis suggested increasing size of molecular aggregation (31.3 nm < 35.2 nm < 2.93 μm) with increase in concentration (10 μg < 17.5 μg < 130 μg). Discussion and conclusions: The study elucidates the antileishmanial potential of SVE against Leishmania donovani promastigotes by exerting oxidative stress and DNA damage. In sum, SVE can be explored as an immunotherapeutic candidate against leishmaniasis and other infectious diseases.